Pengaruh Motivasi, Self-Efficacy, Prospek Kerja, Pengetahuan Perpajakan, Nilai Sosial, dan Persepsi terhadap Minat Mahasiswa Jurusan Akuntansi Menjadi Konsultan Pajak - Izzatul Qudsiyah; Hestin Sri Widiawati; Andy Kurniawan (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This research is motivated by the low interest of accounting students to pursue a career as a tax consultant, even though opportunities in the field of taxation are increasingly wide open. This phenomenon is thought to be influenced by a number of internal and external factors, such as motivation, self-efficacy, job prospects, tax knowledge, social values, and students' perceptions of the tax consultant profession. The purpose of this study is to analyze the influence of these six variables on students' interest in becoming tax consultants, both partially and simultaneously. This study uses a quantitative approach with a comparative causal method. The research sample consisted of 188 accounting students at Universitas Nusantara PGRI Kediri who were taken using a purposive sampling technique. Data were collected through an online questionnaire and analyzed using validity and reliability tests, multiple linear regression analysis, classical assumption tests, t-tests and F-tests. The results of the study indicate that motivation, self-efficacy, job prospects, and perceptions have a significant influence on interest in becoming a tax consultant, while tax knowledge and social values ​​do not have a significant effect. These findings emphasize the importance of psychological factors and perceptions in shaping students' career interests.